Аналіз транспортних затримок на регульованих перехрестях з використанням імітаційного моделювання - Грицунь, Олег; Давосир, Владислав (Видавництво Львівської політехніки, 2018)
In this work is considered analysis of transport delays appearance on regulated intersections. There is clarified understanding the definition “transport delay”, described the ways of solving the problem of road network capacity increasing. There is given mathematical model of transport delays determination on stop lines of traffic light objects, which allows determining rational regimes of regulation in terms of time loss minimization in traffic flows.
Analysis of transport delays on regulated intersections using simulation modelling
Keywords: 653.11